High‐Performance Ultraviolet‐Visible Light‐Sensitive 2D‐MoS2/1D‐ZnO Heterostructure Photodetectors. Issue 11 (19th March 2020) - Zhang, Jian; Liu, Yiting; Zhang, Xinglai; Ma, Zongyi; Li, Jing; Zhang, Cai; Shaikenova, Altynay; Renat, Beisenov; Liu, Baodan
Abstract: Two‐dimensional (2D) transition‐metal dichalcogenides (TMDs) such as molybdenum disulfide (MoS2 ) have recently attracted extensive interest for building future optoelectronic devices. However, the limited light absorption, low photoresponsivity and slow response speed in visible range inhibit their further application. Here, we proposed a promising approach to realize the high‐performance photodetectors (PDs) by constructing 2D‐MoS2 flake/1D‐ZnO nanowire mixed‐dimensional heterostructures. The integration of 1D‐ZnO on p‐type or n‐type MoS2 to form the mixed‐dimensional 2D‐MoS2 /1D‐ZnO heterostructure PDs not only broadens the light response range, but also improves the photoresponsivity and response time of 2D‐MoS2 flakes. Under the 365 nm light illumination, the photoresponsivity, external quantum efficiency and response time of p‐MoS2 /n‐ZnO PDs are as high as 24.36 A/W, 8.28×10 3  % and 0.9 s, respectively. Under 532 nm light illumination, the photoresponsivity, external quantum efficiency and response time are estimated to be 0.35 A/W, 80.9 % and 140 ms, respectively. These properties are superior or comparable to the performance of other reported 2D‐MoS2 flake PDs. This work provides a possible strategy for the realization of high‐performance optoelectronic devices by the integration of 2D‐MoS2 and 1D‐ZnO to form mixed‐dimensional heterostructures. Abstract : The ultraviolet‐visible light‐sensitive photodetectors based on 2D‐MoS2 /1D‐ZnO heterostructures are designed and fabricated. By integrating 1D‐ZnO nanowire with high carrier mobility and excellent UV light response, the photodetection performance of either p‐MoS2 or n‐MoS2 flake PDs is significantly enhanced due to the synergistic effect in both ultraviolet and visible light region.